Frontal Alpha Asymmetry in Children with Trauma Exposure. (September 2022) - Im, Sungjin; Fitzpatrick, Skye; Hien, Denise A.; Lopez-Castro, Teresa; Pawlak, Anthony; Melara, Robert D.
The purpose of the current study was to investigate differences in frontal alpha asymmetry (FAA) between children (5-17 years) with or without histories of trauma exposure. EEG data were obtained from 165 children who participated in the Healthy Brain Network Initiative during rest with eyes open and closed. FAA during resting-state electroencephalography was significantly more negative in the trauma-exposed group, suggesting greater left lateralized FAA and avoidance-oriented motivation. Moreover, alpha suppression (difference in alpha amplitude between eyes open and eyes closed conditions) was marginally greater in the trauma-exposed group. The results suggest that early exposure to trauma may be associated with trait-level avoidance of environmental stimuli, which ultimately may be predictive of psychopathology, including posttraumatic stress disorder (PTSD). Study findings thus provide preliminary evidence of brain-based mechanisms that may confer risk for PTSD in the wake of early trauma exposure.